Impacts of soil fertility on species and phylogenetic turnover in the high - rainfall zone of the Southwest Australian global biodiversity hotspot - Sander, Juliane; Wardell-Johnson, Grant (Springer, 2011)
The ancient landscape of the South - West Australian Floristic Region (SWAFR) is characterized by exceptional floristic diversity, attributed to a complex mosaic of nutrient - impoverished soils. Between - soil type differences in nutrient availability are expected to affect floristic assemblage patterns in the SWAFR. We compared patterns of floristic diversity between open - forest samples from three soil types in the high - rainfall zone of the SWAFR. The importance of environmental and spatial factors for species compositional turnover within soil types were evaluated within canonical correspondence analyses using variation partitioning. Patterns of phylogenetic diversity and dispersion were contrasted between soil types and related to differences in soil nutrient availability. Between - quadrat shared phylogenetic branch length for individual life form categories was correlated with explanatory variables using Mantel tests. Species and phylogenetic diversity increased with a decline in soil nutrients and basal area. Nutrient - poorer soils were differentiated by higher species density and phylogenetic diversity, and larger phylogenetic distances between species. Species turnover was best explained by environmental factors when soil nutrient concentrations and basal area were low. Coastal and inland quadrats from the most fertile soil type were distinguished by significantly differing patterns of phylogenetic diversity.Inland quadrats were characterized by strong relationships between phylogenetic diversity and environment, while phylogenetic patterns remained largely unaccounted for by explanatory variables within coastal quadrats. Phylogenetic diversity was more strongly related with environment within upland landform types for nutrient-poor soils. We highlight the complex relationships between climatic and edaphic factors within the SWAFR, and propose that the occurrence of refugial habitat for plant phylogenetic diversity is dynamically linked with these interactions. Climate change susceptibility was estimated to be especially high for inland locations within the high - rainfall zone. Despite the strong relationship between floristic diversity and soil fertility, holistic conservation approaches are required to conserve the mosaic of soil types regardless of soil nutrient status.